A case study of teaching English as a second language in three rural primary classes. Issue 4 (2nd October 2018) - Omidire, Funke; Ebersöhn, Liesel; Leask, Marisa; Konza, Deslea; du Plessis, Anna-Barbara
Abstract: Assessment results from rural schools have shown little improvement in over a decade, mainly because many of the barriers to learning, such as poverty and limited resources, still prevail. Without the necessary English language skills, language can become another barrier to learning. The assessment results of Progress in International Reading Literacy Studies (PIRLS) in 2011 and 2016 reinforce the need for instructional practices to address the difficulties learners' experience with English in primary school. The aim of our study was to provide a detailed analysis of how English as a second language is taught, to guide policy makers in developing the instructional skills of teachers in rural settings, and consequently to improve the educational outcomes of the learners. A comparative case study was used to provide evidence-based descriptions of the teachers' instructional practices from three Grade 3 classes. Findings indicated that language instruction appeared to focus on the structural components of language, compromising the development of the independent academic language skills needed to make the transition in Grade 4 to English as the language of learning and teaching. The results of this research can inform the planning and monitoring of future literacy development initiatives, and thereby, improve assessment results of learners.